Phylogenetic relationship and characterization of the complete chloroplast genome of Laggera crispata, a folk herbal medicine plant in China. Issue 6 (3rd June 2022) - Zhou, Zhongyu; Pu, Tingting; Duan, Baozhong; Zhang, Manchang
Abstract: Laggera crispata, an herbaceous plant, has been used in Chinese medicines as anti-inflammatory, analgesic, and anti-viral. In this study, the complete chloroplast (cp) genome sequence of L. crispata was first reported. The cp genome of L. crispata is 155522 bp in length, with two inverted repeats (IR) regions of 25042 bp, the large single copy (LSC) region of 84198 bp and the small single copy (SSC) region of 21240 bp. 128 genes were predicted, including 87 protein-coding genes, 37 tRNA genes, and 8 rRNA genes. The phylogenetic analysis suggested that L. crispata is more closely related to Pluchea pteropoda and P. indica with solid bootstrap values belonging to the subfamily Inuleae of Asteraceae.